Changes and Correlation Between Physiological Characteristics of Rhododendron simsii and Soil Microbial Communities Under Heat Stress - Liu, Lei; Lin, Wei; Zhang, Li; Tang, Xuexiao; Liu, Yue; Lan, Siren; Wang, Shusheng; Zhou, Yan; Chen, Xiaochou; Wang, Ling; Chen, Xiang; Guo, Lijin (Frontiers in Plant Science, 2022)
The relationship between Rhododendron simsii and its soil microbial community under heat stress was not clear. In this study, the effects of heat stress on the physiological characteristics, soil physicochemical properties and soil microbial community structure of R. simsii were investigated. The experimental control (CK) was set as day/night (14/10 h) 25/20°C and experimental treatments were set as light heat stress (LHS) 35/30°C and high heat stress (HHS) 40/35°C. Our results showed that, compared with CK, LHS treatment significantly increased malondialdehyde, hydrogen peroxide, proline and soluble sugar contents, as well as catalase and peroxidase activities, while HHS treatment significantly increased ascorbate peroxidase activity and decreased chlorophyll content. Compared with CK, LHS treatment significantly reduced soil ammonium-nitrogen and nitrate-nitrogen content, while HHS significantly increased soil ammonium-nitrogen content. Compared with CK, both treatments changed the soil microbial community structure. For bacterial community, LHS and HHS treatment resulting in the significant enrichment of Burkholderia-Caballeronia-Paraburkholderia and Occallatibacte, respectively. For fungal community, LHS treatment resulting in the significant enrichment of Candida, Mortierella and Boothiomyces. The redundancy analysis showed that plant physiological characteristics, soil ammonium-nitrogen content were significantly correlated with the soil microbial community. Therefore, heat stress altered the soil microbial community structure, and affected the availability of soil available nitrogen, which in turn affected the physiological characteristics of R. simsii. We suggest that soil microbial community may play an important role in plant resistance to heat stress, and its mechanism deserves further study.